Binary Analysis and Period Study of the Long-period, High-mass-ratio Contact Binary KIC 7766185 - Conor M. Larsen; Andrej Prša (The Astronomical Journal)
We present an in-depth photometric and spectroscopic study of the contact binary KIC 7766185. Spectroscopic observations were conducted on the Mayall 4 m telescope at Kitt Peak National Observatory and used to extract radial velocities. Using the radial velocity measurements, Kepler photometry, and Gaia multicolor photometry, binary analysis was performed in PHOEBE to determine orbital and stellar parameters. The results classify KIC 7766185 as an A-type W UMa system and reveal one of the largest and most massive secondary stars in the sample of well studied W UMa systems. The two stars are in a shallow contact state, with a small fillout factor of 0.029 ± 0.002. Along with the binary analysis, we conduct a period study that reveals evidence for a cyclic variation in the eclipse timings.